A Peer-led Diabetes Education Program in a Homeless Community to Improve Diabetes Knowledge and Empowerment. Issue 2 (2nd April 2016) - Davis, Sage; Keep, Suzanne; Edie, Alison; Couzens, Suzan; Pereira, Katherine
ABSTRACT: Peer-led diabetes education has been shown to be as effective, or more effective, than traditional education in improving glycemic control and diabetes self-care measures. A 4-week peer-led diabetes education program was conducted in a homeless community in Grand Rapids, Michigan to increase diabetes knowledge and empowerment. Knowledge scores increased significantly during sessions covering signs, symptoms, and complications of diabetes and diabetes medications ( p s <.05). Empowerment scores after attending the 4-week program were significantly increased when compared to scores prior to the first session ( p = .027). Field notes and postimplementation focus group support increased empowerment and knowledge among participants.